Pengukuran Kecerahan Langit Arah Zenit di Medan dan Serdang Bedagai Menggunakan Sky Quality Meter - Abu Yazid Raisal; Hariyadi Putraga; Muhammad Hidayat; Arwin Juli Rakhmadi (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2021)
Light pollution is a worldwide problem that affects fewer stars that can be seen at night. This study aims to measure the brightness of the sky in the zenith direction to minimize the effect of light pollution in observing celestial bodies. The research used the observation method of sky brightness level with SQM. Measurement of sky brightness was carried out in two places, namely in Medan and Serdang Bedagai. The SQM is mounted in a zenith direction and set to retrieve data every two seconds. Observations were made on November 10-13, 2018, during the new moon phase. The average value of sky brightness obtained in Medan is 18.05 mpsas and the NELM value is 4.00. Based on the Bortle scale, Medan is included in the ninth class area, namely the inner-city sky. Meanwhile, the average value of sky brightness obtained in Serdang Bedagai is 19.69 mpsas and the NELM value is 5.26. Based on the Bortle scale, Serdang Bedagai belongs to the sixth class area, namely bright suburban sky.